Antifreeze Protein‐Induced Selective Crystallization of a New Thermodynamically and Kinetically Less Preferred Molecular Crystal. Issue 47 (9th October 2013) - Wang, Sen; Wen, Xin; Golen, James A.; Arifin, Josh F.; Rheingold, Arnold L.
Abstract The formation of a new, dihydrate crystalline form of 5‐methyluridine (m5U) was selectively induced by a protein additive, antifreeze protein (AFP) in a highly efficient manner (in 10−6 molar scale, whereas known kinetic additives need 0.1 molar scale). The hemihydrate form (form I, the only previously known crystalline form of m5U) and the dihydrate form of m5U (form II) obtained herein were characterized using X‐ray crystallography and differential scanning calorimetry (DSC). Compared to form I, remarkably, form II is thermodynamically and kinetically less preferred. The presence of AFP can selectively inhibit the appearance of form I and hence allows the growth of form II, the pure form of which cannot grow directly from m5U supersaturated solutions under the same conditions. An explanation supported by both experimental and theoretical results is provided for the AFP‐induced selection process. Implications on AFP‐induced ice shape changes are also discussed. Control of crystallization from supersaturated solutions is of great interest in both fundamental research and practical applications in fields like chemistry, pharmacology and materials science. These findings suggest that crystallization processes with AFPs could be valuable for selective growth of hydrates and polymorphs of important pharmaceutical compounds.